The impact of computerized accounting information system on Small and Medium Enterprises (SMEs) performance in Mogadishu, Somalia - Abdulle, Abdisalam Salad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
The adoption of Information and Communication Technology (ICT) has increased dramatically over time in the domain of public and private organizations, as well as profit and non-profit organizations around the world. ICT investment has spurred the economic growth as evidenced in the existing literature. The African Union Agenda 2063 acknowledges the importance of digital inclusivity for African countries to be at par with the rest of the world as information society. In the business environment where businesses are competing in a highly fragile market, the use of computerized accounting software in capturing and monitoring all business processes is crucial for ensuring continuous improvement towards competitive services offered to customers. The implementation and adoption of Computerized Accounting Information Systems (CAIS) by any organizations, including Small and Medium Enterprises (SMEs), will enable the management and owners to improve decision making and financial information; it will also enhance the internal controls and enables financial reporting to be designed and processed according to the standardized format and on timely basis. However, it has been reported that the use of inefficient information and poor quality and reliability of financial information to support the financial decision makers are the major challenges faced by SMEs. In the context of SMEs in Somalia, they are currently facing challenges to deploy ICT on the issues of availability, accessibility, and affordability. Therefore, this study attempts to understand the usage of CAIS and identify its impact on the performance of SMEs. A survey questionnaire was designed and distributed to the selected SMEs in the capital city of Somalia – Mogadishu. The results on the impact of CAIS are discussed from the perspective of balanced scorecard's components, namely financial, customer, internal processes and, innovation and learning. The outcome of this study will provide a definite knowledge on the impact of CAIS usage onto SMEs performance in Somalia. Besides, the findings of this study are expected to allow various agencies in Somalia to render assistance for SMEs in adopting higher level of CAIS.